Stomach content analysis of Pristolepis grooti from the Koto Panjang Dam and Bencah Kelubi swamp - Efizon, Deni; ', Zainudin; ', Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Pristolepis grooti (Anabantidae) is a freshwater fish that commonly present in the flooded swamp area along the river and also in the dam. This fish has relatively low economical value, but it is protein source for villagers. Information on biological aspects, including the type of food consumed by the fish is rare. To understand the stomach content of the fish, a study has been conducted from February to April 2015. The fish was sampled from the swamp area in the Bencah Kelubi Village and from the Koto Panjang Dam, 6 times, once/ week. The stomach content of the fish was then identified and the Preponderance Index (Natarajan and Jhingran, 1961) was calculated. Results shown that the main food of fish from those sampling sites are different. The main food of the Koto Panjang fish was fish feed pellets remains (PI 56.53%) , while that of the swamp fish was insects (98.67%). Data obtained from this research shown that P. grooti is able to consume many types of food available.Keyword :Pristolepis grooti, Koto Panjang dam, Bencah Kelubi, stomach content, fish feed pellet.